A MEMS Flow Compensated Thermal Conductivity Detector for Gas Sensing. (2015) - de Graaf, G.; Abarca, A.; Ghaderi, M.; Wolffenbuttel, R.F.
Abstract: A novel dual-Thermal conductivity detector (TCD) is presented for in-line flow compensation. TCDs generally demonstrate a flow dependence requiring calibration at a fixed flow rate. This dual-TCD is composed of two thin-film sensors on membranes in parallel on the same chip that are differentially operated. Both are laterally identical, but with a difference in quasi-static thermal conductivity by a different sample chamber. A reduced flow rate dependence is possible under conditions described in this work. Simulations of the dual-TCD that verify its operation are presented. The device is fabricated using both bulk and surface micromachining. Currently, prototypes are being fabricated and measurements results are forthcoming.